Optimizing Slaughterhouse Waste as Liquid Organic Fertilizer: An Organic Solution to Enhance Cayenne Pepper Production - Hariyanto, Hariyanto; Hadiyanti, Nugraheni; Kustiani, Edy; Nurcahyo, Agung Wilis (Kadiri University - Faculty of Agriculture, 2025)
Cattle rumen waste from slaughterhouses holds economic, social, and ecological value when processed into liquid organic fertilizer (LOF). The application of this LOF has the potential to improve soil fertility, thereby enhancing plant growth and productivity. A collaborative study between the Agrotechnology Study Program of Universitas Kadiri and the Slaughterhouse Technical Unit (UPTD RPH) of Kediri City was conducted to evaluate the effect of LOF derived from cattle rumen waste on the growth and yield of cayenne pepper (Capsicum frutescens L.). The research was carried out from October 2022 to January 2023 in the greenhouse of the Geophysics Station (BMKG) located in Sawahan Village, Sawahan Subdistrict, Nganjuk Regency. The experiment used a completely randomized design (CRD) with a single factor: LOF dosage, consisting of six treatment levels: D0 (control), D1 (100 ml/plant), D2 (200 ml/plant), D3 (300 ml/plant), D4 (400 ml/plant), and D5 (500 ml/plant) with four replications. Each experimental unit comprised two plants. Observed parameters included plant height, stem diameter, number of leaves, number of branches, and fruit number and weight. Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at a 5% significance level. The results indicated that the 500 ml/plant dosage had a highly significant effect on plant height and stem diameter, and a significant effect on the number of branches, but no effect on leaf number. Notably, increasing LOF dosage significantly improved fruit number and weight by 27% at 90 days after transplanting (DAT).